A small-molecule acceptor incorporating a silicon bridging atom for efficient nonfullerene polymer solar cells. Issue 48 (15th November 2018) - Zeng, Guang; Ouyang, Jinyang; Xin, Yue; Zhao, Xiaoli; Yang, Xiaoniu
Abstract : The acceptorSi4TIC-F, which incorporated a silicon bridging atom, was synthesized and gave a PCE of 10.20% with the donorPBTIBDTT . Abstract : Recently, there have been rapid advances in polymer solar cells (PSCs) based on nonfullerene small-molecule acceptors (n-SMAs) due to their outstanding properties. Silicon, which is a member of group 14 in the periodic table, may endow small-molecule acceptors with unique properties, especially when it is incorporated into conjugated backbones. In this work, a narrow band gap n-SMA based on a dithienosilole (DTS) unit incorporating silicon bridging atom, namedSi4TIC-F, was designed and synthesized.Si4TIC-F has a rigid, planar conjugated backbone, benefiting intermolecular stacking and charge transport. PairingSi4TIC-F with a wide band gap copolymer, poly[4, 8-bis(5-(2-ethylhexyl)thiophen-2-yl)benzo[1, 2- b :4, 5- b ′]-dithiophene- alt-N -(2-hexyldecyl)-5′5-bis[3-(decylthio)thiophene-2-yl]-2′2-bithiophene-3′3-dicarboximide] (PBTIBDTT ), achieved a power conversion efficiency (PCE) of 10.2%. The PCE is much better than those of other systems with DTS-based acceptors. Our results demonstrate the potential of the classical DTS unit in constructing new n-SMAs to realize high-performance nonfullerene PSCs, which will help advance the development of PSCs.